Analytics for Hospital Resource Planning—Two Case Studies. Issue 6 (11th February 2020) - Xie, Jingui; Zhuang, Weifen; Ang, Marcus; Chou, Mabel C.; Luo, Li; Yao, David D.
Abstract : Using real data and process flows from two large hospitals (in Singapore and in Chengdu, China) as cases, we illustrate how to apply certain modeling and optimization techniques, along with simulation as a validation tool, to hospital resource planning problems. We demonstrate how these simple analytical tools can help achieve significant improvements in both patient service and resource utilization, and without the need to increase the overall level of existing capacities. Two resource planning problems are studied in detail, one concerns the rebalancing of bed capacities among various wards, and the other addresses the allocation of medical diagnostic resource among different types of patients.